THE CONCEPT OF FOREGROUNDING IN THE WAKE OF THE DEVELOPMENTS OF STYLISTICS - Tevdoradze, Nino (Online Journal of Humanities ETAGTSU, 2023)
The concept of foregrounding occupied much of Jakobson’s time stylistics. Through the influence of later and recent developments in the field of stylistics, this concept has undergone deep alteration and has been taken to a new level. This paper aims to discuss, on the one hand, its emergence and evolution. On the other, it endeavors to examine its validity from today’s perspective. Full Text (PDF)